Effects of Nutrition Education Alone and in Combination with Homestead Food Production on Nutritional Status and School Performance among Rural Students of Kishoreganj - Zebsyn, Sonia; Hossain, Md Towhid; Bhuyan, Md Aminul Haque (Bangladesh Journal of Nutrition, 2019)
The research critically evaluated the sequence of homestead food production (HFP) inputs along with nutrition education program and also the effect of only the latter on nutritional status and school performance in chosen rural secondary school pupils of Kishoreganj district of Bangladesh. In this research, a total of 1214 pupils were distributed among study group 1, study group 2 and the control group. The number of students in study group 1, study group 2 and the control group was406, 400 and 408 respectively. The study group 1 took part in the nutrition education program. The second study group received HFP inputs besides nutrition education. Anthropometric, blood samples and school performance-related data were gathered at the beginning and also after an intervention of six months. In the control group, severe and moderate malnutrition increased at the end of the research period of half a year (from 2.0 to 2.5% and 8.9 to 10.5% respectively). On the other hand, severe and moderate malnutrition reduced in study group 1 (from 8.5 to 6.4% and 13.5 to 11.3%respectively) and study group 2 (from 4.5 to 4.2% and 10.1 to 8.3% respectively) after the intervention. The prevalence of anemia was 48.5%, 43.8% and 48.5% at the baseline in the control, first and second study groups respectively. After half-year, the frequency of anemia escalated in the control group (54.9%) while it reduced in the study group 1 (35.5%) and study group 2 (44%). The serum ferritin level reduced from baseline in the control group. Noteworthy differences in the examination marks were noted in the three groups after the duration of six months, especially among the pupils in study groups 1 and 2. Advancement in curricular achievement of study group 2 was noticeably better than study group 1(p<0.05) and control group (p<0.05). Findings from this study suggest nutrition intervention programs can positively affect the nutritional status and the academic performance of the students. Bangladesh J. Nutr. Vol. 32, December 2019, P: 5-13